A revised synthesis of 6-alkoxy-2-aminopurines with late-stage convergence allowing for increased molecular complexity. (24th August 2022) - Mader, Lavleen; Hayward, John J.; Porter, Lisa A.; Trant, John F.
Abstract : This streamlined synthesis allows the alcohol at the 6-position of 6-alkoxy-2-arylaminopurines to be used only in moderate excess, rather than as solvent, opening up the possibility of accessing more complicated molecules. Abstract : 6-Alkoxy-2-aminopurine derivatives are potent inhibitors of Cyclin Dependent Kinases (CDKs), with some selectivity towards CDK2 and thus have potential as cancer therapeutics. Development of these inhibitors for targeting CDK2-cyclin A/E complexes has previously involved a thorough investigation of structure activity relationships of the C-2 amine moiety. However, the established synthesis of these compounds, which uses the alcohol reagent as solvent, limits the complexity of the O-6 functionality which is required for more selective targeting. Herein we report an improved and refocused synthesis of a model CDK2 inhibitor (NU6247), affording convenient access to inhibitors with O-6 substituents whose parent alcohol is not amenable for use as solvent. This revised synthesis allows for a meaningful exploration of the O-6 position in this class of CDK2 inhibitors.